2022
DOI: 10.1177/1420326x211051414
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxygen supply and oxygen distribution on single-head tunnel with different altitudes under mixed ventilation

Abstract: Hypoxia plays a major role in limiting the construction of the high-altitude mine. Understanding the effect and the distribution of diffused oxygen supply at different altitudes is the premise for the design of a mine with oxygen supply system and the full utilization of oxygen resources. For the optimal design of an oxygen supply mode and ventilation system, a multi-component fluid model of the diffused oxygen supply of a single-head tunnel was developed. This study reveals the variation law of the average ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…The advantages of this invention are that the installation position of the fan is fixed, the length of the pipeline is long, but there are problems such as slow smoke exhaust rate and high ventilation energy consumption. The method of pipeline ventilation is to set a ventilation hole near the front of the drilling hole that passes through the ventilation pipe, in order to discharge the unclean gas in the drilling hole into the front end of the drilling hole [6]. This method has the advantage of good smoke exhaust effect, but there is a need to move the position of the roadway and ventilation device forward, which affects engineering construction.…”
Section: Current Status Of Tunnel Construction Ventilation Technologymentioning
confidence: 99%
“…The advantages of this invention are that the installation position of the fan is fixed, the length of the pipeline is long, but there are problems such as slow smoke exhaust rate and high ventilation energy consumption. The method of pipeline ventilation is to set a ventilation hole near the front of the drilling hole that passes through the ventilation pipe, in order to discharge the unclean gas in the drilling hole into the front end of the drilling hole [6]. This method has the advantage of good smoke exhaust effect, but there is a need to move the position of the roadway and ventilation device forward, which affects engineering construction.…”
Section: Current Status Of Tunnel Construction Ventilation Technologymentioning
confidence: 99%
“…The specific location of the mine is shown in Figure 1 . A number of scholars have investigated the environmental characteristics and production situation of the Pulang copper mine, and have taken it as an example to conduct research on roadway ventilation [ 17 , 18 , 31 ]. The setting of atmospheric pressure, air density, and temperature can be directly referenced by these studies.…”
Section: Numerical Analysismentioning
confidence: 99%
“…Atmospheric pressure, air density, and air temperature were set to the same parameters as the Pulang copper mine roadway model [18]. The k-epsilon turbulence model is suitable for solving exterior flow problems involving complex geometry [26,34], and a number of scholars have experimentally verified that the realizable k-epsilon model is suitable and accurate for the study of oxygen supply ventilation systems [17]; hence, the realizable k-epsilon model is adopted in this paper. The realizable k-epsilon model considers two equation models that deal with turbulent kinetic energy, k, and its rate of dissipation, ε, which are coupled with turbulent viscosity.…”
Section: Boundary Conditions and Turbulence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…West et al [19] illustrated that indoor oxygenation would benefit people at high altitudes by analogy to air conditioning regulation for oxygen regulation. Li et al [20] developed a multi-component fluid model for diffusive oxygen supply in single-headed tunnels to optimize the oxygen supply method and ventilation system design, and concluded that the oxygen mass fraction distribution in single-headed tunnels showed a similar trend of increasing and then decreasing at different altitudes. Li et al [21] used computational fluid dynamics methods to explore the optimal type of oxygen supply pipe outlet based on field data from the Pulang Copper Mine in Yunnan Province, revealing the oxygen diffusion pattern affecting different ventilation factors.…”
Section: Introductionmentioning
confidence: 99%